Exploring the Impact of Trust in Leader and Knowledge Sharing on Employee Innovation - Novitasari, Dewiana; Supriatna, Heri; Asbari, Masduki; Nugroho, Yunianto Agung; Nadeak, Multi (International Journal of Social and Management Studies, 2021)
This study investigates the impact of trust-in leaders within employees in the manufacturing industry in Indonesia towards employee innovation and checks on the impact of mediation from knowledge sharing to this relationship. 121 employees in the manufacturing industry participate in this research. The result of research claimed that trust-in leader has a positive and significant effect on knowledge sharing and employee innovation. Likewise, knowledge sharing has a positive and significant effect on employee innovation. Therefore, the result of the research showed that knowledge sharing has a partial mediation impact on the relationship between trust-in leader and employee innovation.